Respiratory involvement in inflammatory bowel diseases - D'Andrea Nadia; Vigliarolo Rossana; Sanguinetti Claudio M (Multidisciplinary Respiratory Medicine, 2010)
Abstract Inflammatory bowel diseases (IBD) include ulcerative colitis (UC) and Crohn's disease (CD) and are due to a dysregulation of the antimicrobial defense normally provided by the intestinal mucosa. This inflammatory process may extend outside the bowel to many organs and also to the respiratory tract. The respiratory involvement in IBD may be completely asymptomatic and detected only at lung function assessment, or it may present as bronchial disease or lung parenchymal alterations. Corticosteroids, both systemic and aerosolized, are the mainstay of the therapeutical approach, while antibiotics must be also administered in the case of infectious and suppurative processes, whose sequels sometimes require surgical intervention. The relatively high incidence of bronchopulmonary complications in IBD suggests the need for a careful investigation of these patients in order to detect a possible respiratory involvement, even when they are asymptomatic.